Answer:
98 nickles and 128 pennies
Step-by-step explanation:
You probably can't read my hand writing but I spent like, 15 minutes on this. This is the correct answer, but I don't know how to explain how it is but I promise it is!
2. x^2 +6x +8 = (x+4)(x+2)
3. x^2 -7x +12 = (x-4)(x-3)
4. g^2 -2g -24 = (g+4)(g-6)
hope helped
We have that
<span>tan(theta)sin(theta)+cos(theta)=sec(theta)
</span><span>[sin(theta)/cos(theta)] sin(theta)+cos(theta)=sec(theta)
</span>[sin²<span>(theta)/cos(theta)]+cos(theta)=sec(theta)
</span><span>the next step in this proof
is </span>write cos(theta)=cos²<span>(theta)/cos(theta) to find a common denominator
so
</span>[sin²(theta)/cos(theta)]+[cos²(theta)/cos(theta)]=sec(theta)<span>
</span>{[sin²(theta)+cos²(theta)]/cos(theta)}=sec(theta)<span>
remember that
</span>sin²(theta)+cos²(theta)=1
{[sin²(theta)+cos²(theta)]/cos(theta)}------------> 1/cos(theta)
and
1/cos(theta)=sec(theta)-------------> is ok
the answer is the option <span>B.)
He should write cos(theta)=cos^2(theta)/cos(theta) to find a common denominator.</span>
1*n-10 = (5/6)*n-((1/3)*n)-7 // - (5/6)*n-((1/3)*n)-7
1*n-((5/6)*n)+(1/3)*n-10+7 = 0
n+(-5/6)*n+(1/3)*n-10+7 = 0
1/2*n-3 = 0 // + 3
1/2*n = 3 // : 1/2
n = 3/1/2
n = 6
That's just in case you had to show your work lol^^
Answer:
70
Step-by-step explanation:
Substitute x with -6:
2(-6)²-2
2(36)-2
72-2
70